Design and Implementation of Gypsum Mixing Machine - Al-Sharif, Raed; Etkaidek, Mohammad; Ghannam, Ammar (جامعة بوليتكنك فلسطين - اتمتة صناعية, 2018)
يهدف هذا المشروع للخروج بماكينة تعمل على خلط الجبص المحضر يدويا, لتقليل الجهد الالزم لعملية تحضير خليط الجبص وايضا زيادة القدرة االنتاجية وتوفير بيئة عمل صحية مناسبة للعامل وكذلك الحصول على خليط ذو جودة عالية وذلك من خالل تصميم وبناء ماكينة مؤتمتة بشكل كامل. تم دراسة اّلية عمل الماكينات المستخدمة عالمياًلتوزين وتعبئة الجبصوكذلك اليات عملية خلط المزيج و شروطها وبعدها تم تحديد التصميم الميكانيكي و المعدات واألجهزة الالزمة لبناء هذا المشروع وتم بعدها تنفيذ الماكنة عمليا. بعد تنفيذ الماكنه عمليا تم اجراء عدة اختبارات للماكينة لفحص جودة مخرجاتها وسالمة تصميمها حيث تم الخروج بماكينة و قد حققت اهداف المشروع كاملة متمثلة بانتاج خليط الجبص بوقت اقل ودقة اعلى من عملية الخلط اليدوية وزادت القدرة االنتاجية وحافظت على سالمة بيئة العمل من غبار الجبص الضار وقللت الفاقد في المادة الخام لذلك نعتبر مشروعنا ناجح من كل النواحي. IV Abstract “Design and Implementation of Weighing and Mixing Gypsum” This project is intended to produce a full automatic machine that mix the gypsum with water, instead of being prepared manually. This leads to saving effort and time in preparing the mixture, from one hand this increases the capacity of production, allows healthy working conditions, comfortable to the worker and provides a mixture with high quality. A study has been conducted on similar machines that are used worldwide to weight and pack gypsum, also the mechanism of mixing the ingredient (gypsum and water), and the ideal conditions for running the process. Accordingly, the mechanical designing and the equipment needed for the completing of the project have been determined, and implemented to form the mentioned machine. After completely building the machine, several tests have been conducted to the quality of the product, and the safety of the machine components to ensure that the machine meets all the goals and conditions for accurate quality and healthy productions. So, the conducted tests and validation satisfy the project requirement and achieved results. So, we humbly consider our project a complete success.
no of pages 250 , CD , اتمتة صناعية 4/2018 , in the store
Keywords: Gypsum Mixing Machine